Mummies, myth, and magic in ancient Egypt - El Mahdy, Christine (New York, N.Y. : Thames and Hudson, 1989)
Describes the origins and purpose of mummification, clears up misconceptions about mummies, and looks at recent scientific studies.
Includes bibliographical references.
Keywords: Mummies -- Egypt; Funeral rites and ceremonies -- Egypt; Magic, Egyptian; Momies -- 2; z; Egyptian mummies, ancient period